Does digital village construction promote rural residents’ happiness? - Zou, Meifeng; Gao, Yunfeng; Ma, Hua; Zhang, Yuefei (Frontiers in Sustainable Food Systems, 2025)
Digital village construction (DVC) is a new form of development that uses emerging digital technologies and brings change to rural residents. This paper delves into the influence and mechanism of DVC on rural resident happiness utilizing the ordered Probit model, drawing on data from the China Family Panel Studies (CFPS). Our findings indicate a marked enhancement in rural residents well-being as a consequence of DVC, and the results remain robust after replacing OLS regression, changing the measurement of explanatory and explained variables, adding other control variables, and using CMP estimation. Heterogeneity analysis shows that the enhancement effect is significant in male, middle-aged and highly educated groups, while the effect is insignificant for young groups, low and middle education groups. The mechanism tests show that the DVC can improve the rural residents’ happiness by increasing household income and reducing the loneliness. Government might amplify its investment and bolster digital infrastructure, enabling a greater number of rural residents to fully benefit from the development of a digital countryside.